Chromium-free zinc-aluminum coating and application thereof

By using double-layer coating structure and nanomaterials in chromium-free zinc-aluminum coatings, the problems of high energy consumption and limited use environment are solved, and a coating with high hardness and good antibacteriality is achieved to adapt to the variable outdoor environment.

CN119614080APending Publication Date: 2025-03-14SHENHUA RAIL & FREIGHT WAGONS TRANSPORT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411871066.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing chromium-free zinc-aluminum coatings can only be cured by high temperature heating, which consumes high energy and is limited in use, so they cannot adapt to the variable outdoor environment.

Method used

The double-layer coating structure is adopted. The first coating is composed of zinc powder, aluminum powder, nickel powder and epoxy modified silicone resin. The second coating contains nano zinc and nano copper. It forms a high hardness and good antibacterial coating by curing at room temperature.

Benefits of technology

It improves the corrosion resistance, antibacteriality and durability of the coating, reduces curing temperature and energy consumption, adapts to more usage environments, and simplifies production and construction conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614080A_ABST
    Figure CN119614080A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating protection, and discloses a chromium-free zinc-aluminum coating and application thereof. The chromium-free zinc-aluminum coating comprises a coating I and a coating II, the coating I comprises a liquid A and a liquid B; the liquid A comprises zinc powder, aluminum powder, nickel powder and a solvent I; the liquid B comprises epoxy modified silicon resin, and the epoxy modified silicon resin is obtained by carrying out grafting reaction on hydroxyl acrylic resin containing double bonds and a siloxane prepolymer; the coating II comprises liquid D, liquid E and a curing agent; the liquid D comprises nano-zinc, nano-copper and a solvent II; the liquid E comprises epoxy resin, a solvent III and an optional auxiliary III. By forming a double-layer coating, protection on a matrix is strengthened, and the corrosion resistance and durability of the coating are improved. The coating II contains nano-zinc and nano-copper, so that the corrosion resistance and antibacterial property of the coating in a humid environment are improved; when a corrosive medium invades, zinc and copper can form a primary battery, and the zinc easily loses electrons, so that the zinc serves as an anode to sacrifice to protect a substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating protection, and in particular to a chromium-free zinc-aluminum coating and application thereof. Background Art

[0002] With the continuous progress of material civilization, people have higher and higher requirements for the quality of living environment. Protecting and improving the ecological environment and achieving sustainable economic and social development have become the value orientation of most countries in formulating development strategies for the new century. Due to the harm of hexavalent chromium to people and the environment, after entering the 1990s, major automobile manufacturers in the European Community proposed to reduce or even eliminate hexavalent chromium ions in the coating when performing surface treatment on automobile parts, and relevant drafts were also proposed. Some relevant regulations have been promulgated at home and abroad to limit or prohibit the use of hexavalent chromium.

[0003] In 1999, Europe passed a regulation on scrapped cars and their accessories. This regulation, called "End of life Vehicle Directive (EOLVD)", officially came into effect in 2006. Articles 4.2 and 6.3 of the regulation restrict the use of hazardous substances such as lead, mercury, cadmium, and hexavalent chromium. The introduction of this regulation has put forward higher environmental protection requirements for the surface treatment of automotive parts, making the Dacromet coating technology currently widely used in the automotive manufacturing industry face severe challenges.

[0004] Chromium-free zinc-aluminum-nickel alloy coating is developed based on Dacromet technology. The coating mainly uses chromium substitute as binder. After coating and film formation, it can achieve the same excellent anti-corrosion performance as Dacromet, but the coating does not contain Cr at all. 6+ , truly achieve green treatment Si on the surface of the material. Therefore, the development of chromium-free zinc-aluminum-nickel alloy coatings that meet the requirements is a research hotspot for technicians in related fields.

[0005] Existing chromium-free zinc-aluminum coatings can only be cured by high-temperature heating. High-temperature heating curing consumes a lot of energy and has strict requirements on the curing environment, which is not suitable for changeable outdoor use environments. Summary of the invention

[0006] The present invention provides a chromium-free zinc-aluminum coating and its application to solve the technical problems that the prior art only uses high temperature curing, high energy consumption and limited use environment. The chromium-free zinc-aluminum coating of the present invention can form a double-layer coating, which can effectively improve the hardness and adhesion of the coating surface, and at the same time improve the corrosion resistance and antibacterial properties, and has universal applicability.

[0007] The first object of the present invention is to provide a chrome-free zinc-aluminum coating, which comprises a coating I for forming a first coating and a coating II for forming a second coating;

[0008] The coating I comprises liquid A and liquid B; the liquid A comprises zinc powder, aluminum powder, nickel powder and solvent I; the liquid B comprises epoxy-modified silicone resin, which is obtained by grafting a hydroxy acrylic resin containing double bonds with a siloxane prepolymer;

[0009] The coating II includes liquid D, liquid E and a curing agent; the liquid D includes nano zinc, nano copper and solvent II; preferably, the weight ratio of liquid D to liquid E is (0.5-1.5): (8-9.5);

[0010] The E liquid comprises epoxy resin, solvent III and optional auxiliary agent III.

[0011] According to a preferred embodiment of the present invention, the coating I further comprises a curing agent;

[0012] Preferably, the curing agent includes at least one of 650 low molecular weight polyamide and curing agent T-31;

[0013] And / or, the curing agent accounts for 5-15wt%, preferably 9-11wt% of the total mass of coating I.

[0014] The coating formed by the present invention completely eliminates hexavalent chromium and trivalent chromium that are harmful to the environment and human body, realizes clean production, and the coating has no flash point, no flammability and no explosion. No strict fire prevention measures are required during production, transportation and construction, which greatly simplifies production and construction conditions and improves safety performance.

[0015] The epoxy-modified silicone resin of the present invention is obtained by grafting a hydroxy acrylic resin containing double bonds with a siloxane prepolymer. The "double bond" in the hydroxy acrylic resin refers to an unsaturated double bond present in the resin molecule, usually a carbon-carbon double bond (C=C). This unsaturated double bond allows the hydroxy acrylic resin to form a cured network structure through free radical polymerization or cross-linking reaction with other reactive compounds (such as isocyanates, epoxy compounds, etc.).

[0016] Compared with the polymer formed by the grafting reaction of the single-bond hydroxy acrylic resin and the siloxane prepolymer, the epoxy-modified silicone resin obtained by the grafting reaction of the double-bond hydroxy acrylic resin and the siloxane prepolymer of the present invention has the following advantages:

[0017] a Cross-linking performance: The polymer formed by the grafting reaction of double-bond hydroxyl acrylic resin and siloxane prepolymer usually has a higher degree of cross-linking, thus providing better heat resistance, chemical resistance and weather resistance.

[0018] B. Physical Properties: This polymer has better physical properties such as hardness, strength and wear resistance, making it more competitive in a wide range of applications.

[0019] c. Interface bonding: Due to the presence of cross-linked structures, this polymer can better bond with different substrate surfaces, providing more reliable coating performance and adhesion.

[0020] d. Functional adjustment: By adjusting the ratio of hydroxy acrylic resin to siloxane prepolymer and the reaction conditions, the properties of the polymer can be flexibly adjusted to meet the requirements of different applications.

[0021] The polymer obtained by grafting double-bond hydroxy acrylic resin with siloxane prepolymer has advantages in cross-linking degree, physical properties, interface bonding and functional adjustment, and therefore has broad application prospects in the fields of coatings, sealants, adhesives, etc.

[0022] The epoxy-modified silicone resin of the present invention is a material obtained by changing the structure of an organic silicone resin, specifically, it is prepared by a grafting reaction of a hydroxy acrylic resin containing a double bond and a siloxane prepolymer, and has super weather resistance, boiling water resistance, solvent resistance, polar medium resistance, pollution resistance, high toughness, and good physical and mechanical properties of the paint film.

[0023] In addition, the first coating of the present invention uses a cross-linking reaction during the drying and film-forming process to form a three-dimensional network structure. Epoxy-modified silicone resin contains epoxy groups and siloxane groups, which are interconnected by chemical bonds or physical cross-linking points, thereby forming a stable polymer network structure. At the same time, it forms a complex with the surface of the metal substrate, such as steel, so that the iron atoms on the surface of the steel also become a component of the inorganic macromolecular structure of the coating, thereby forming a strong chemical bond, so that the coating has a good bonding force with the steel, and at the same time, the wear resistance of the film layer is greatly improved, and the hardness of the coating surface is not less than 9H; the solution of adding a curing agent can be cured at room temperature, and the hardness is not less than 7H, which can fully meet the needs of actual production.

[0024] In the second coating of the present invention, the nano copper and zinc used are safer than various metal ions such as hexavalent chromium. Nano copper and zinc show strong antibacterial properties to microorganisms when the concentration is extremely low (nanomolar or micromolar), and the toxicity to mammals is relatively low, and complications rarely occur. Nano zinc and nano copper can achieve physical sterilization, and have good persistence. Nano copper and zinc can be loaded on carriers such as resins, and when objects are attacked by bacteria, copper ions and zinc ions are continuously released, and relatively stable concentration is maintained to achieve the purpose of lasting antibacterial. Furthermore, the body and axle surfaces of the nano copper and zinc oily coatings containing high antibacterial properties have the function of antibacterial sterilization, reduce the corrosion of bacteria to objects, ensure the safety of equipment use, and extend the service life of equipment. When the corrosive medium invades, zinc and copper can form a primary battery, and zinc is more likely to lose electronics, thereby protecting the matrix as an anode sacrifice.

[0025] In the present invention, the nano copper and nano zinc used show more active chemical properties than ordinary copper and zinc. Nano materials usually do not change the state of matter, but their intrinsic properties may change. The bactericidal mechanism of copper and zinc is: copper and zinc can release ions in water medium, among which copper ions and zinc ions have strong redox effects. Under aerobic conditions, copper and zinc react with water to produce hydroxyl radicals (-OH) and active oxygen ions (O 2- ). These ions can destroy the protein structure of microbial cells and inhibit cell proliferation, thereby achieving bactericidal and antibacterial effects.

[0026] In addition, nano-copper and nano-zinc can improve the flame retardancy of the resin, enhance the mechanical properties of the resin, and improve its impact resistance and wear resistance.

[0027] According to a preferred embodiment of the present invention, in the coating I, the weight ratio of the A liquid to the B liquid is 62:(35-39);

[0028] And / or, in parts by weight, the liquid A comprises the following components: 20-26 parts of zinc powder, 3-6 parts of aluminum powder, 0.1-0.5 parts of nickel powder, and 23-43 parts of solvent I;

[0029] And / or, the zinc powder is flaky zinc powder with a length of 10-15 μm and a width of 0.2-0.3 μm;

[0030] And / or, the aluminum powder is flake aluminum powder with a length of 5-25 μm and a width of 0.1-0.4 μm;

[0031] And / or, the average particle size of the nickel powder is 60-100 nm;

[0032] And / or, the solvent I is a mixture of dimethyl carbonate and dibasic ester; preferably, the mass ratio of dimethyl carbonate to dibasic ester is 1:1-7:3; including but not limited to 1:1, 1.5:1, 1.8:1, 2:1, 7:3.

[0033] And / or, the B liquid epoxy-modified silicone resin is epoxy-modified resin SMH-30.

[0034] The present invention adopts flaky zinc powder, flaky aluminum powder and nickel powder. In the process of forming the film layer, the metal powders are superimposed layer by layer, which sets up a barrier between the substrate and the external corrosive medium, effectively protects the substrate and plays a role in multi-metal corrosion protection.

[0035] According to a preferred embodiment of the present invention, in the D solution, the concentration of the nano zinc is 900-1100 ppm, and the concentration of the nano copper is 900-1100 ppm;

[0036] And / or, the nano zinc is prepared by reducing a zinc source with a reducing agent; preferably, the zinc source includes at least one of zinc nitrate, zinc oxide, zinc nitrate, zinc acetate, and zinc sulfate; and / or, the reducing agent is sodium borohydride or potassium borohydride;

[0037] And / or, the nano copper particle size is 50-80 nm; the nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd.;

[0038] And / or, the solvent II is at least one of methanol, ethanol and acetone.

[0039] Specifically, the synthesis steps of nano zinc are as follows: after mixing a thickening dispersant with an organic solvent, a zinc source is added and stirred evenly, and then a reducing agent is added and stirred for 30-60 minutes to obtain the nano zinc.

[0040] Preferably, the mass ratio of the thickening dispersant to the organic solvent is (0.5-1.2):100; the mass ratio of the zinc source to the organic solvent is (0.5-1):1000; and the mass ratio of the reducing agent to the zinc source is (0.8-1.2):10.

[0041] Preferably, the thickening dispersant includes at least one of cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylamide, polyvinyl pyrrolidone and carbopol resin.

[0042] According to a preferred embodiment of the present invention, in the liquid E,

[0043] The mass ratio of the epoxy resin, solvent III and auxiliary agent III is (55-78): (20-43): (2-3);

[0044] The epoxy resin is E44 epoxy resin or 711 epoxy resin, preferably 711 epoxy resin;

[0045] And / or, the auxiliary agent III is at least one of a leveling agent, a coupling agent and a defoaming agent;

[0046] And / or, the solvent III is at least one of kerosene D60, dibasic acid ester and xylene.

[0047] According to a preferred embodiment of the present invention, the liquid A further comprises an auxiliary agent I;

[0048] Preferably, the auxiliary agent I includes at least one of a leveling agent, a coupling agent, and a defoaming agent;

[0049] And / or, in parts by weight, the additive I in the liquid A is 0.1-7 parts;

[0050] And / or, the liquid B further comprises an auxiliary agent II;

[0051] Preferably, the auxiliary agent II includes at least one of a silane coupling agent and an adhesion promoter;

[0052] And / or, by weight, the additive II in the liquid B is 0.5-5 parts.

[0053] According to a preferred embodiment of the present invention, the adhesion promoter is a phosphate adhesion promoter;

[0054] Preferably, the phosphate adhesion promoter is selected from at least one of dimethoxy phosphate, trimethoxy phosphate, and G40 from RAHN Company of Switzerland.

[0055] The present invention adopts epoxy modified silicone resin. The main chain of epoxy modified silicone resin is Si-OH+RO-Si, and the side groups include methyl, ethyl, vinyl and other substituents. When cross-linked and cured with silane coupling agent, metal powder and the like, a polycondensation reaction will occur, and the substituents will be replaced by other groups, thereby forming a network structure of macromolecular chains, which are covered layer by layer on the substrate, thereby protecting the substrate. The hydroxyl groups in the epoxy modified silicone resin participate in the reaction, and the epoxy groups are retained. The prepared anti-corrosion coating has the advantages of silicone resin and epoxy, and has super weather resistance, boiling water resistance, solvent resistance, polar medium resistance, pollution resistance, high toughness, good physical and mechanical properties of the paint film, and good corrosion resistance. Photoinitiator is selected to reduce the high electricity cost caused by high temperature baking. The use of silane coupling agent and phosphate adhesion promoter can improve the adhesion of the coating to the metal surface, provide excellent adhesion, and provide service life.

[0056] The content of silane coupling agent and phosphate adhesion promoter is usually determined according to the specific application requirements and formula design. The amount is not the more the better, but needs to be reasonably controlled according to the required performance and effect.

[0057] According to a preferred embodiment of the present invention, the curing agent used in coating I and coating II is the same.

[0058] The second object of the present invention is to provide an application of chromium-free zinc-aluminum coating in surface treatment of metal-based materials.

[0059] According to a preferred embodiment of the present invention, the processing method comprises the following steps:

[0060] First, coating the surface of the substrate with coating I and drying it to form a first coating; then coating the surface of the first coating with coating II and drying it to obtain a second coating;

[0061] Preferably, the surface of the metal substrate is subjected to rust removal and drying treatment before coating I is applied;

[0062] Preferably, the thickness of the first coating is 2-8 μm, preferably 2-3 μm; the thickness of the second coating is 1-6 μm, preferably 1-2 μm.

[0063] According to a preferred embodiment of the present invention, when the coating I does not contain a curing agent, the method for forming the first coating comprises: stirring the coating I evenly, applying it to the surface of the substrate, curing it at 200-240° C. for 25-60 minutes, and cooling it to room temperature to obtain a substrate containing the first coating;

[0064] Or, when the coating I contains a curing agent, the method for forming the first coating comprises: after the coating I is stirred evenly, it is applied to the surface of the substrate, and it is cured at 120-150° C. for 120-180 minutes and cooled to room temperature, or cured at room temperature for 72 hours to obtain a substrate containing the first coating;

[0065] The method for forming the second coating layer comprises: mixing and stirring the coating II, applying the coating to the substrate containing the first coating layer, curing the coating at room temperature for 10-48 hours, and forming a film on the substrate to obtain a substrate containing a double coating layer.

[0066] The beneficial effects of the present invention are as follows: the chromium-free zinc-aluminum coating of the present invention comprises coating I and coating II, and a double-layer coating is formed by sequentially coating coating I and coating II on the surface of a metal substrate, thereby strengthening the protection of the substrate and improving the corrosion resistance and durability of the coating. At the same time, coating II contains nano zinc and nano copper, which improve the corrosion resistance and antibacterial properties of the coating in a humid environment; in addition, when a corrosive medium invades, zinc and copper will form a primary battery, and zinc will more easily lose electrons, thereby acting as an anode sacrifice to protect the substrate.

[0067] The present invention reduces the curing temperature by adding a curing agent, and the coating II can be cured at room temperature. The hardness of the obtained coating is ≥7H (the hardness is tested according to GB6739-86), which reduces the high electricity cost caused by high-temperature baking and reduces energy consumption. In addition, because high-temperature curing is avoided, the requirements for the curing environment are reduced, and it can adapt to more usage environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 The following are pictures of the substrate surface before and after treatment in Example 1 of the present invention. In the figure: a, is a picture before treatment, b, is a picture after treatment.

[0069] Figure 2 The following are pictures of the substrate surface before and after treatment in Example 2 of the present invention. In the figure: a, is a picture before treatment, b, is a picture after treatment.

[0070] Figure 3 The following are pictures of the substrate surface before and after treatment in Example 3 of the present invention. In the figure: a, is a picture before treatment, b, is a picture after treatment.

[0071] Figure 4 This is a picture of a sample after surface treatment at one end of Example 4 of the present invention.

[0072] Figure 5 These are pictures of samples before and after surface treatment in Example 5 of the present invention.

[0073] Figure 6 The following are pictures of the substrate surface before and after treatment in Example 6 of the present invention. In the figure: a, is the picture before treatment, b, is the picture after treatment.

[0074] Figure 7 The following are pictures of the substrate surface before and after treatment in Example 7 of the present invention. In the figure: a, is a picture before treatment, b, is a picture after treatment.

[0075] Figure 8 The salt spray resistance effect of the coating without coating of the present invention and the coating treated by Example 4 is compared. In the figure: a is a picture of the sample without coating after 100 hours of salt spray, and b is a picture of the coating of Example 4 after 100 hours of test salt spray.

[0076] Fig. 9 The following is the result of the coating of Example 4 after 480 hours of neutral salt spray test.

[0077] Fig.10 The antibacterial performance diagram of the coating corresponding to Embodiment 4 of the present invention is shown in FIG. a, which is a diagram of the solution before the bacteria-containing solution flows through the coating; and b, which is a diagram of the solution after the bacteria-containing solution flows through the coating.

[0078] Fig.11 The antibacterial performance diagram of the coating corresponding to Embodiment 2 of the present invention is shown in FIG. a, which is a diagram of the solution before the bacteria-containing solution flows through the coating; and b, which is a diagram of the solution after the bacteria-containing solution flows through the coating.

[0079] Fig.12 This is a cross-cut test diagram of the coating of Example 7. DETAILED DESCRIPTION

[0080] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0081] In the following examples, all products used are commercially available.

[0082] [Example 1]

[0083] The chromium-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A and liquid B, and coating Ⅱ includes independently packaged liquid D, liquid E and curing agent T-31;

[0084] In coating Ⅰ, the mass ratio of liquid A to liquid B is 62:38.

[0085] The raw materials and weight proportions of each raw material contained in liquid A are as follows: 20 parts of zinc powder (flaky, 10-15 μm long, 0.2-0.3 μm wide), 6 parts of aluminum powder (flaky, 5-25 μm long, 0.1-0.4 μm wide), 0.1 parts of nickel powder (average particle size 80 nm), 43 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio 1:1), 0.1 parts of leveling agent BYK-301, 2 parts of coupling agent a-silicon 28, and 0.4 parts of defoaming agent BYK-051N. The above raw materials are mixed evenly to obtain liquid A.

[0086] The raw materials contained in liquid B and the weight proportions of each raw material are: 28 parts of epoxy modified silicone resin, 0.5 parts of silane coupling agent KH560, and 1 part of phosphate adhesion promoter dimethoxy phosphate (DMP). The above raw materials are mixed evenly to obtain liquid B.

[0087] In coating II, the mass ratio of liquid D to liquid E is 1:9, and the mass fraction of the curing agent in coating II is 10%.

[0088] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0089] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 1:100, stirring, adding zinc nitrate at a mass ratio of 1:100 to ethanol, stirring evenly again, adding sodium borohydride at a mass ratio of 1:10 to zinc nitrate, and stirring for 45 minutes. Nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components are mixed to obtain liquid D.

[0090] Liquid E includes the following components by weight percentage: 65% 711 epoxy resin, 33% solvent III dibasic acid ester, 2% additives (0.5% leveling agent BYK-301, 1% coupling agent silicon 28, 0.5% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0091] The application process method of treating a metal substrate using the combined product of this embodiment includes the following steps:

[0092] (1) preparing a 25 wt % aqueous solution of a reducing rust remover, spraying the rust remover on the surface of the rusted metal substrate, and then drying at a temperature of 70° C. for 3 min;

[0093] (2) Liquid A and Liquid B are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), cured at 220° C. for 45 min, and cooled to room temperature to obtain a substrate containing a first coating layer, wherein the thickness of the first coating layer is 3 μm.

[0094] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 15 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 2 μm.

[0095] like Figure 1 The rusty metal substrate shown in Figure a is treated by the above steps to obtain the treated sample as shown in Figure a. Figure 1 As shown in Figure b.

[0096] [Example 2]

[0097] The chrome-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A and liquid B, and coating Ⅱ includes independently packaged liquid D, liquid E and curing agent T-31;

[0098] In coating Ⅰ, the mass ratio of liquid A to liquid B is 62:38.

[0099] Among them, the raw materials contained in liquid A and the weight proportion of each raw material are: 26 parts of zinc powder (flake, length 10-15μm, width 0.2-0.3μm), 3 parts of aluminum powder (flake, length 5-25μm, width 0.1-0.4μm), 0.5 parts of nickel powder (average particle size 80nm), 38 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio of 7:3), 0.3 parts of leveling agent BZ-602, 6 parts of coupling agent a792, and 0.1 parts of defoaming agent BYK-051N; the above raw materials are evenly mixed to obtain liquid A.

[0100] The raw materials contained in liquid B and the weight proportions of each raw material are: 30 parts of epoxy modified silicone resin, 1.0 part of silane coupling agent KH-580, and 1 part of trimethoxy phosphate (TMP), a phosphate adhesion promoter; the above raw materials are mixed evenly to obtain liquid B.

[0101] In coating II, the mass ratio of liquid D to liquid E is 1:9.5, and the mass fraction of the curing agent in coating II is 10%.

[0102] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0103] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 1.2:100, stirring, adding zinc nitrate at a mass ratio of 1.2:100, stirring evenly again, adding sodium borohydride at a mass ratio of 1.2:10, and stirring for 60 minutes. Nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components are mixed to obtain liquid D.

[0104] Liquid E includes the following components by mass percentage: 55% 711 epoxy resin, 42% solvent III dibasic acid ester, 3% additives (0.5% leveling agent BYK-301, 1.5% coupling agent Silicon 28, 1% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0105] The process for treating a metal substrate using the combined product of this embodiment comprises the following steps:

[0106] (1) a reducing rust remover is prepared into a 25 wt % aqueous solution, and then the rusty metal substrate is immersed or sprayed on the surface of the rusty metal substrate, and then dried at a temperature of 60° C. for 5 min;

[0107] (2) Liquid A and Liquid B are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), cured at 220° C. for 60 min, and cooled to room temperature to obtain a substrate containing a first coating layer, wherein the thickness of the first coating layer is 3 μm.

[0108] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 20 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 2 μm.

[0109] like Figure 2 After the rusty metal substrate shown in the figure is treated by the above steps, the treated sample is as shown in FIG. Figure 2 shown.

[0110] [Example 3]

[0111] The chromium-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A and liquid B, and coating Ⅱ includes independently packaged liquid D, liquid E, and curing agent 650 low molecular weight polyamide;

[0112] In coating Ⅰ, the mass ratio of liquid A to liquid B is 62:38.

[0113] Among them, the raw materials contained in liquid A and the weight proportion of each raw material are: 24 parts of zinc powder (flake, length 10-15μm, width 0.2-0.3μm), 4 parts of aluminum powder (flake, length 5-25μm, width 0.1-0.4μm), 0.5 parts of nickel powder (average particle size 80nm), 30 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio of 2:1), 0.3 parts of leveling agent BZ-602, 4 parts of coupling agent a-silicon 40, and 0.5 parts of defoaming agent BYK-051N; the above raw materials are evenly mixed to obtain liquid A.

[0114] The raw materials contained in liquid B and the weight proportions of each raw material are: 32 parts of epoxy modified silicone resin, 1.2 parts of silane coupling agent KH560, and 3 parts of the phosphate adhesion promoter dimethoxy phosphate (DMP); the above raw materials are mixed evenly to obtain liquid B.

[0115] In coating II, the mass ratio of liquid D to liquid E is 0.5:9, and the mass fraction of the curing agent in coating II is 10%.

[0116] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0117] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 0.5:100, stirring, adding zinc nitrate at a mass ratio of 0.5:100, stirring evenly again, adding sodium borohydride at a mass ratio of 0.8:10, and stirring for 45 minutes. Nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components are mixed to obtain liquid D.

[0118] Liquid E includes the following components by mass percentage: 78% 711 epoxy resin, 20% solvent III dibasic acid ester, 2% additives (0.5% leveling agent BYK-301, 1% coupling agent silicon 28, 0.5% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0119] The process for treating a metal substrate using the combined product of this embodiment comprises the following steps:

[0120] (1) a reducing rust remover is prepared into a 25 wt % aqueous solution, and then the rusty metal substrate is immersed or sprayed on the surface of the rusty metal substrate, and then dried at a temperature of 50° C. for 5 min;

[0121] (2) Liquid A and Liquid B are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), cured at 240° C. for 25 min, and cooled to room temperature to obtain a substrate containing a first coating layer, wherein the thickness of the first coating layer is 2 μm.

[0122] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 10 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 1 μm.

[0123] like Figure 3 After the rusty metal substrate shown in Figure a is treated by the above steps, the treated sample is as follows: Figure 3 As shown in Figure b.

[0124] [Example 4]

[0125] The chromium-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A, liquid B and curing agent T-31, and coating Ⅱ includes independently packaged liquid D, liquid E and curing agent T-31;

[0126] In coating I, the mass ratio of liquid A to liquid B is 62:38, and the mass fraction of the curing agent is 10%.

[0127] Among them, the raw materials contained in liquid A and the weight proportion of each raw material are: 20 parts of zinc powder (flake, length 10-15μm, width 0.2-0.3μm), 6 parts of aluminum powder (flake, length 5-25μm, width 0.1-0.4μm), 0.1 parts of nickel powder (average particle size 80nm), 45 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio of 1:1), 0.1 parts of leveling agent RG-5305, 2 parts of coupling agent a vinyl trimethoxy silane, and 0.4 parts of defoaming agent BYK-051N; the above raw materials are mixed evenly to obtain liquid A.

[0128] The raw materials contained in liquid B and the weight proportion of each raw material are: 28 parts of epoxy modified silicone resin, 0.5 parts of silane coupling agent vinyl trimethoxy silane, and 1 part of the phosphate adhesion promoter dimethoxy phosphate (DMP). The above raw materials are mixed evenly to obtain liquid B.

[0129] In coating II, the mass ratio of liquid D to liquid E is 1:9, and the mass fraction of the curing agent in coating II is 10%.

[0130] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0131] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 1:100, stirring, adding zinc nitrate at a mass ratio of 1:100 to ethanol, stirring evenly again, adding sodium borohydride at a mass ratio of 1:10 to zinc nitrate, and stirring for 45 minutes. Nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components are mixed to obtain liquid D.

[0132] Liquid E includes the following components by mass percentage: 65% 711 epoxy resin, 33% solvent III dibasic acid ester, 2% additives (0.5% leveling agent BYK-301, 1% coupling agent silicon 28, 0.5% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0133] The process for treating a metal substrate using the combined product of this embodiment comprises the following steps:

[0134] (1) preparing a 25 wt % aqueous solution of a reducing rust remover, then immersing or spraying the rusted metal substrate on the surface of the rusted metal substrate, and then drying at a temperature of 70° C. for 3 min;

[0135] (2) Liquid A, liquid B and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), cured at 150° C. for 120 min, and cooled to room temperature to obtain a substrate with a first coating. The thickness of the first coating is 3 μm.

[0136] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 15 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 2 μm.

[0137] One end of the rusty metal substrate was treated by the above steps (the other end was not treated), and the surface treated sample was obtained as shown in FIG. Figure 4 shown.

[0138] [Example 5]

[0139] The chromium-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A, liquid B and curing agent T-31, and coating Ⅱ includes independently packaged liquid D, liquid E and curing agent T-31;

[0140] In coating I, the mass ratio of liquid A to liquid B is 11:9, and the mass fraction of the curing agent is 10%.

[0141] The raw materials and weight proportions of each raw material contained in liquid A are as follows: 20 parts of zinc powder (flaky, 10-15 μm long, 0.2-0.3 μm wide), 6 parts of aluminum powder (flaky, 5-25 μm long, 0.1-0.4 μm wide), 0.1 parts of nickel powder (average particle size 80 nm), 45 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio 1:1), 0.1 parts of leveling agent BZ-602, 2 parts of coupling agent a792, and 0.4 parts of defoaming agent BYK-053N. The above raw materials are mixed evenly to obtain liquid A.

[0142] The raw materials contained in liquid B and the weight proportions of each raw material are: 28 parts of epoxy modified silicone resin, 0.5 parts of silane coupling agent silicon KH560, and 1 part of the phosphate adhesion promoter dimethoxy phosphate (DMP); the above raw materials are mixed evenly to obtain liquid B.

[0143] In coating II, the mass ratio of liquid D to liquid E is 1:9, and the mass fraction of the curing agent in coating II is 10%.

[0144] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0145] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 1:100, stirring, adding zinc nitrate at a mass ratio of 1:100 to ethanol, stirring evenly again, adding sodium borohydride at a mass ratio of 1:10 to zinc nitrate, and stirring for 45 minutes. Nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components are mixed to obtain liquid D.

[0146] Liquid E includes the following components by mass percentage: 65% 711 epoxy resin, 33% solvent III dibasic acid ester, 2% additives (0.5% leveling agent BYK-301, 1% coupling agent silicon 28, 0.5% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0147] The process for treating a metal substrate using the combined product of this embodiment comprises the following steps:

[0148] (1) A reducing rust remover is prepared into a 50 wt% aqueous solution, a cloth is soaked in the rust remover, and then the rusty metal pipe is wrapped, and then sealed with a plastic cloth. After 60 minutes, the plastic cloth is unsealed, and the dissolved residue on the surface is scrubbed with the cloth, and then the rust is neutralized with a neutralizing rust preventive working solution, and the pipe is dried naturally;

[0149] (2) Liquid A, liquid B and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), and cured at room temperature for 72 hours, and cooled to room temperature to obtain a substrate containing a first coating. The thickness of the first coating is 3 μm.

[0150] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 48 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 2 μm.

[0151] like Figure 5 After the rusty metal substrate shown in Figure a is treated by the above steps, the treated sample is as follows: Figure 5 As shown in Figure b. The pipeline in this embodiment is a natural gas pipeline. The pipeline with natural gas is not suitable for high-temperature curing under laboratory conditions. On the one hand, the pipeline is large in volume and connected to other pipelines. It is not suitable for movement and can only be processed in situ. On the other hand, the natural gas pipeline is filled with hot air, which is flammable and explosive and not suitable for high-temperature curing. This embodiment obtains a double-layer coating through conventional curing, which can achieve the protection of substrates that cannot be used for high-temperature curing.

[0152] [Example 6]

[0153] The chromium-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A, liquid B and curing agent T-31, and coating Ⅱ includes independently packaged liquid D, liquid E and curing agent T-31;

[0154] In coating I, the mass ratio of liquid A to liquid B is 11:9, and the mass fraction of the curing agent is 10%.

[0155] The raw materials and weight proportions of each raw material contained in liquid A are as follows: 20 parts of zinc powder (flaky, 10-15 μm long, 0.2-0.3 μm wide), 6 parts of aluminum powder (flaky, 5-25 μm long, 0.1-0.4 μm wide), 0.1 parts of nickel powder (average particle size 80 nm), 45 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio 1:1), 0.1 parts of leveling agent BZ-602, 2 parts of coupling agent a792, and 0.4 parts of defoaming agent BYK-053N. The above raw materials are mixed evenly to obtain liquid A.

[0156] The raw materials contained in liquid B and the weight proportions of each raw material are: 28 parts of epoxy modified silicone resin, 0.5 parts of silane coupling agent silicon KH560, and 1 part of the phosphate adhesion promoter dimethoxy phosphate (DMP); the above raw materials are mixed evenly to obtain liquid B.

[0157] In coating II, the mass ratio of liquid D to liquid E is 1.2:8.8, and the mass fraction of the curing agent in coating II is 10%.

[0158] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0159] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 1:100, stirring, adding zinc nitrate at a mass ratio of 1:100 to ethanol, stirring evenly again, adding sodium borohydride at a mass ratio of 1:10 to zinc nitrate, and stirring for 45 minutes. Nano copper is purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components are mixed to obtain liquid D.

[0160] Liquid E includes the following components by mass percentage: 65% 711 epoxy resin, 33% solvent III dibasic acid ester, 2% additives (0.5% leveling agent BYK-301, 1% coupling agent silicon 28, 0.5% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0161] The process for treating a metal substrate using the combined product of this embodiment comprises the following steps:

[0162] (1) Prepare a 5wt% aqueous solution of cleaning and rust preventive agent C-1002, heat it to 50°C, use high pressure (5-6 kg water pressure) to clean for 3 minutes, then rinse with a 50°C 5wt% aqueous solution of cleaning and rust preventive agent C-1002 for 3 minutes, and bake at 70°C for 3-5 minutes;

[0163] (2) Liquid A, liquid B and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), baked at 140° C. for 120 min, and cured at room temperature for 48 h to obtain a substrate with a first coating. The thickness of the first coating is 3 μm.

[0164] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 15 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 2 μm. Figure 6 The following are pictures of the substrate surface before and after treatment in Example 6 of the present invention. In the figure: a, is the picture before treatment, b, is the picture after treatment.

[0165] [Example 7]

[0166] The chromium-free zinc-aluminum coating includes coating Ⅰ and coating Ⅱ; coating Ⅰ includes independently packaged liquid A and liquid B, and coating Ⅱ includes independently packaged liquid D, liquid E and curing agent C;

[0167] In coating I, the mass ratio of liquid A to liquid B is 11:9, and the mass ratio of the total mass of liquid A and liquid B to the mass ratio of the curing agent is 87:13.

[0168] The raw materials and weight proportions of each raw material contained in liquid A are as follows: 20 parts of zinc powder (flaky, 10-15 μm long, 0.2-0.3 μm wide), 6 parts of aluminum powder (flaky, 5-25 μm long, 0.1-0.4 μm wide), 0.1 parts of nickel powder (average particle size 80 nm), 45 parts of solvent (dimethyl carbonate and mixed dibasic acid ester DBE, mass ratio 1:1), 0.1 parts of leveling agent BZ-602, 2 parts of coupling agent a792, and 0.4 parts of defoaming agent BYK-053N. The above raw materials are mixed evenly to obtain liquid A.

[0169] The raw materials contained in liquid B and the weight proportions of each raw material are: 28 parts of epoxy modified silicone resin, 0.5 parts of silane coupling agent silicon KH560, and 1 part of the phosphate adhesion promoter dimethoxy phosphate (DMP); the above raw materials are mixed evenly to obtain liquid B.

[0170] In coating II, the mass ratio of liquid D to liquid E is 1.5:8.5, and the mass fraction of the curing agent in coating II is 15%.

[0171] Liquid D includes nano zinc, nano copper and acetone, wherein the concentration of nano zinc in liquid D is 1000 ppm, and the concentration of nano copper is 1000 ppm.

[0172] The nano zinc is prepared by dissolving hydroxyethyl cellulose in ethanol at a mass ratio of 1:100, stirring, adding zinc nitrate at a mass ratio of 1:100 to ethanol, stirring evenly again, adding sodium borohydride at a mass ratio of 1:10 to zinc nitrate, and stirring for 45 minutes. Nano copper was purchased from Beijing Dekedaojin Technology Co., Ltd., with a particle size of 50-80nm. The above components were mixed to obtain liquid D.

[0173] Liquid E includes the following components by mass percentage: 65% 711 epoxy resin, 33% solvent III dibasic acid ester, 2% additives (0.5% leveling agent BYK-301, 1% coupling agent silicon 28, 0.5% defoaming agent BYK-051N); the above components are mixed to obtain Liquid E.

[0174] The process for treating a metal substrate using the combined product of this embodiment comprises the following steps:

[0175] (1) Use a sandblasting machine to remove the rust on the surface of the parts for 45 minutes

[0176] (2) Liquid A, liquid B and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (1), and cured at room temperature for 72 hours to obtain a substrate with a first coating. The thickness of the first coating is 3 μm.

[0177] (3) Liquid D, liquid E and curing agent are mixed in proportion and stirred, and then coated on the metal substrate treated in step (2), and cured at room temperature for 15 hours. The coating forms a film on the substrate to obtain a substrate containing a second coating layer. The thickness of the second coating layer is 2 μm. Figure 7 The following are pictures of the substrate surface before and after treatment in Example 7 of the present invention. In the figure: a, is a picture before treatment, b, is a picture after treatment.

[0178] [Comparative Example 1]

[0179] The only difference between Comparative Example 1 and Example 5 is that Comparative Example 1 contains only coating I but not coating II.

[0180] [Comparative Example 2]

[0181] The only difference between Comparative Example 2 and Example 5 is that Comparative Example 2 contains only coating II but not coating I.

[0182] [Comparative Example 3]

[0183] The only difference between Comparative Example 3 and Example 5 is that the D solution in Comparative Example 3 does not contain nano copper, but only contains nano zinc and an organic solvent, and the concentration of nano zinc is 1000 ppm.

[0184] [Comparative Example 4]

[0185] The only difference between Comparative Example 4 and Example 5 is that the D solution in Comparative Example 4 does not contain nano-zinc, but only contains nano-copper and an organic solvent, and the concentration of nano-copper is 1000 ppm.

[0186] [Comparative Example 5]

[0187] The only difference between Comparative Example 5 and Example 5 is that the curing agent in Comparative Example 5 is replaced by curing agent T520.

[0188] [Comparative Example 6]

[0189] The only difference between Comparative Example 6 and Example 5 is that: in this comparative example, coating I and coating II are directly mixed to prepare a single layer (Example 5 is a two-layer structure in which coating I forms the second coating and coating II forms the second coating); the amount of each component remains unchanged, and the coating thickness is 5 μm.

[0190] Test example:

[0191] The coatings formed on the substrates obtained in the examples and comparative examples were subjected to performance tests, wherein the adhesion was tested using the cross-hatch method (ASTM D3359).

[0192] The salt spray test is to test the salt spray resistance of the substrate samples containing the coating prepared in the examples and comparative examples with a 3% sodium chloride salt solution. During the test, the substrate is placed in a salt spray box at a temperature of 50°C ± 2°C and a humidity of 80%. The salt spray box is turned on to test the corrosion, rust spots and fading of the sample surface. When rust spots begin to appear on the surface, it is judged as the limit time of salt spray resistance. The test results are shown in Table 1.

[0193] Bactericidal performance test: Through the culture method of bacterial culture dishes, an aqueous solution containing a certain proportion of Vibrio concentration was cultured and flowed over a surface containing a nano-zinc-copper coating. The bacterial content at the water inlet and outlet was observed under a microscope, and the bactericidal rate was detected and calculated. The bactericidal rate (%) = (the number of bacteria at the water inlet - the number of bacteria at the water outlet) * 100% / the number of bacteria at the water inlet. The results are shown in Table 1.

[0194] Table 1 Coating test of the embodiment

[0195]

[0196]

[0197] As can be seen from Table 1, the curing temperature of the coating composition of the present invention is lower than that of the prior art. When both the first coating and the second coating contain a curing agent, they can be cured at room temperature and the coating has good adhesion, salt spray resistance and antibacterial properties.

[0198] The double coating prepared by using coating I and coating II at the same time avoids the corrosion of the substrate surface after the coating surface is damaged. Comparative Examples 1-2 only contain coating I or coating II, lacking the protection of the double coating. At this time, the salt spray resistance of the coating will deteriorate, and when it only contains coating I, it does not have antibacterial properties. Comparative Examples 3-4 only contain nano zinc or nano copper. At this time, the primary battery cannot be formed, and the antibacterial property of the coating drops sharply. Comparative Example 5 changes the type of curing agent. At this time, the adhesion is reduced and the salt spray resistance is reduced. When the coating contains coating I and coating II and components, but the preparation process does not use two layers of coating, but a single coating is prepared by mixing, the antibacterial property of the coating will decrease.

[0199] The present invention also tests the salt spray resistance of the coating under different test environments. After the mixed solution containing dust suppressant, antifreeze and high-sulfur coal was dripped onto the surface of the uncoated substrate and the coated substrate prepared in Example 4, the substrate was placed in a salt spray chamber for salt spray test. The mass ratio of the mixed solution of dust suppressant, antifreeze and high-sulfur coal was 1:1:1, and the sulfur content of the high-sulfur coal was 33211.8 mg / kg. The results are as follows: Figure 8 As shown, Figure 8The dark circles are the surfaces of the salt spray test where dust suppressant, antifreeze and high-sulfur coal solution were added. The results show that the coating of the present application has excellent corrosion resistance after 100 hours of salt spray in the environment containing dust suppressant, antifreeze and high-sulfur coal solution. The surface treated with the mixed solution without coating has severe corrosion points and surface corrosion after 100 hours of salt spray.

[0200] Fig. 9 The coating of Example 4 of the present invention was subjected to a 480-hour neutral salt spray test. It can be seen that no rust spots appeared on the coating surface after 480 hours of salt spray.

[0201] The present invention also tests the bacteria content of the bacterial solution after the bacterial solution flows through the coating of Example 2 and Example 4 respectively. The specific method is: collect a water sample containing Vibrio, filter it and apply the sample to the surface of the culture medium, culture it at 25±2℃ and 70±5% humidity for 48 hours, and obtain a solution containing bacteria, in which bacterial spores can be seen with the naked eye. The bacterial solution is flowed through the surface of the substrate prepared in Example 4 and Example 2 respectively, and photos are taken to record the photos of the bacterial solution before flowing in and the photos of the solution flowing out after passing through the surface of the substrate. The results are as follows: Fig.10 , 11 As shown. Fig.11 It can be seen that the amount of bacteria in the solution containing bacteria is significantly reduced after passing through the surface of the substrate of Example 4 of the present invention. The amount of bacteria in the bacterial culture dish in Figure a is the amount of bacteria at the water inlet, and the amount of bacteria at the water outlet is shown in Figure b. Fig.11 The number of bacteria on the surface of the substrate when the bacterial solution passes through the coating prepared in Example 2. Figure a shows the number of bacteria at the water inlet in the bacterial culture dish, and Figure b shows the number of bacteria at the water outlet. It can be seen that the bactericidal rate of the coating prepared in Example 2 is lower than that of Example 4, indicating that the amount of D solution containing nano zinc and copper is reduced, and its antibacterial effect is significantly weakened.

[0202] Fig.12 The cross-cut test diagram of the coating of Example 7 is shown. The cross-cut test is to use a steel sheet to cross-cut the substrate and then peel it off with a blade. Even when the steel sheet is peeled off, the coating can still maintain good adhesion.

[0203] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values ​​from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed minimum and maximum values ​​are considered to have been disclosed.

[0204] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A chromium-free zinc-aluminum coating, characterized in that: The chromium-free zinc-aluminum coating comprises coating I for forming a first coating and coating II for forming a second coating; The coating I comprises liquid A and liquid B; the liquid A comprises zinc powder, aluminum powder, nickel powder and solvent I; the liquid B comprises epoxy-modified silicone resin, which is obtained by grafting a hydroxy acrylic resin containing double bonds with a siloxane prepolymer; The coating II includes liquid D, liquid E and a curing agent; the liquid D includes nano zinc, nano copper and solvent II; The E liquid comprises epoxy resin, solvent III and optional auxiliary agent III.

2. The chromium-free zinc-aluminum coating according to claim 1, characterized in that: The coating I also includes a curing agent; Preferably, the curing agent includes at least one of 650 low molecular weight polyamide and curing agent T-31; And / or, the curing agent accounts for 5-15wt% of the total mass of coating I, preferably 9-11wt%.

3. The chromium-free zinc-aluminum coating according to claim 1 or 2, characterized in that: In the coating I, the weight ratio of the liquid A to the liquid B is 62:(35-39); And / or, in parts by weight, the liquid A comprises the following components: 20-26 parts of zinc powder, 3-6 parts of aluminum powder, 0.1-0.5 parts of nickel powder, and 23-43 parts of solvent I; And / or, the zinc powder is flaky zinc powder with a length of 10-15 μm and a width of 0.2-0.3 μm; And / or, the aluminum powder is flake aluminum powder with a length of 5-25 μm and a width of 0.1-0.4 μm; And / or, the average particle size of the nickel powder is 60-100 nm; And / or, the solvent I is a mixture of dimethyl carbonate and dibasic acid ester; preferably, the mass ratio of dimethyl carbonate to dibasic acid ester is 1:1-7:

3.

4. The chromium-free zinc-aluminum coating according to claim 1 or 2, characterized in that: In the D solution, the concentration of the nano zinc is 900-1100 ppm, and the concentration of the nano copper is 900-1100 ppm; And / or, the nano zinc is prepared by reducing a zinc source with a reducing agent; preferably, the zinc source includes at least one of zinc nitrate, zinc oxide, zinc nitrate, zinc acetate and zinc sulfate; and / or, the reducing agent is sodium borohydride or potassium borohydride; And / or, the nano copper particle size is 50-80nm; And / or, the solvent II is at least one of methanol, ethanol and acetone.

5. The chromium-free zinc-aluminum coating according to claim 1 or 2, characterized in that: In the E solution, The mass ratio of the epoxy resin, solvent III and auxiliary agent III is (55-78): (20-43): (2-3); And / or, the auxiliary agent III is at least one of a leveling agent, a coupling agent and a defoaming agent; And / or, the solvent III is at least one of kerosene D60, dibasic acid ester and xylene.

6. The chromium-free zinc-aluminum coating according to claim 1 or 2, characterized in that: The liquid A also includes an auxiliary agent I; Preferably, the auxiliary agent I includes at least one of a leveling agent, a coupling agent, and a defoaming agent; And / or, in parts by weight, the additive I in the liquid A is 0.1-7 parts; And / or, the liquid B further comprises an auxiliary agent II; Preferably, the auxiliary agent II includes at least one of a silane coupling agent and an adhesion promoter; And / or, by weight, the additive II in the liquid B is 0.5-5 parts.

7. The chromium-free zinc-aluminum coating according to claim 6, characterized in that: The adhesion promoter is a phosphate adhesion promoter; Preferably, the phosphate adhesion promoter is selected from at least one of dimethoxy phosphate, trimethoxy phosphate, and G40 from RAHN Company of Switzerland.

8. Use of the chromium-free zinc-aluminum coating according to any one of claims 1 to 7 in surface treatment of metal-based materials.

9. The use according to claim 8, characterized in that: The processing method comprises the following steps: First, coating the surface of the substrate with coating I to form a first coating; then coating the surface of the first coating with coating II to obtain a second coating; Preferably, the surface of the metal substrate is subjected to rust removal and drying treatment before coating I is applied; Preferably, the thickness of the first coating is 2-8 μm, preferably 2-3 μm; the thickness of the second coating is 1-6 μm, preferably 1-2 μm.

10. The use according to claim 9, characterized in that: When the coating I does not contain a curing agent, the method for forming the first coating comprises: stirring the coating I evenly, applying it on the surface of the substrate, curing it at 200-240° C. for 25-60 minutes, and cooling it to room temperature to obtain a substrate containing the first coating; Or, when the coating I contains a curing agent, the method for forming the first coating comprises: after the coating I is stirred evenly, it is applied to the surface of the substrate, and it is cured at 120-150° C. for 120-180 minutes and cooled to room temperature, or cured at room temperature for 72 hours to obtain a substrate containing the first coating; The second coating is formed by mixing and stirring the coating II, coating it on the substrate containing the first coating, and curing it at room temperature for 10-48 hours, so that the coating forms a film on the substrate to obtain a substrate containing a double coating.